Development and Validation of the Sinonasal Outcome Test-12 - Salma S. Al Sharhan; Mohammed H. Al Bar; Abdulmalik S. Al Saied; Maha I. Al Somali; Moataza M. Abdel Wahab (SAGE Publishing, 2023)
Objectives: Quality of life (QoL) questionnaires are widely used in clinical interviews to assess the impact of medical interventions or measure the outcomes of healthcare services. The main aim of such questionnaires is the subjective assessment of health status and its impact on QoL. This study aimed to develop an efficient, short sinonasal disease assessment instrument, the sinonasal outcomes test-12 (SNOT-12), and to compare it with the preexisting SNOT-22. Methods: This was a two-phase cross-sectional study. The study was performed between June 2019 and February 2020 using the electronic files of the ORL department outpatient clinics at King Fahd University Hospital, affiliated with Imam Abdulrahman Bin Faisal University. The study was performed in 2 phases: an item reduction phase, which resulted in an initial SNOT-12 scale, and a validation phase, using a comparative analysis of the initial SNOT-12 and the SNOT-22. Results: The developed short-form SNOT-12 maintained the 4 latent factors extracted in EFA (nasal, Sleep/extra nasal, psychological, ear/facial). It strongly correlated with SNOT-22 ( r  = 0.973). It had good construct reliability (0.705-0.901) and validity and a higher discrimination power than the SNOT-22. Conclusions: The SNOT-12 is a short, valid, and reliable instrument that may prove useful for the initial screening and monitoring of patients with chronic rhinosinusitis.